Metafizyczne doświadczenie niestałej Arche - Piotr Sikora (Analiza i Egzystencja, 2018)
METAPHYSICAL EXPERIENCE OF THE VARIABLE ARCHE Summary In my paper I sketch a conception of metaphysical experience as the experience of Arche – a ground of being and existence. I argue that Arche is unstable and fluid, but hidden beneath our everyday, commonsense experiences of the world consisting of beings with firmly established identities. I also sketch the way leading from that everyday experience of the world towards the experience of the hidden Arche.